2004
DOI: 10.1111/j.1472-765x.2003.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Liquid culture carbon, nitrogen and inorganic phosphate source regulate nematicidal activity by fluorescent pseudomonads in vitro

Abstract: Aims:  The aim of the present investigation was to determine the influence of nutrients on the nematicidal activity by Pseudomonas aeruginosa strain IE‐6S+ and Ps. fluorescens strain CHA0 in vitro. Methods and Results:  Culture filtrate of IE‐6S+ and CHA0 obtained from chemically defined medium caused mortality of Meloidogyne javanica juveniles in vitro and that growth medium amended with various C, N or inorganic phosphate (Pi) sources markedly influenced nematicidal activity of the two bacteria. Glycerol (C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…This resulted in poor growth and no production of DAPG, independent of the inorganic nitrogen source. These results are in contrast to results obtained by Siddiqui and Shaukat [ 26 ], who observed a nematicidal activity of filtrate from the DAPG-producing strain CHA0 when cultured on a medium lacking organic nitrogen. However, in their study it was not confirmed that the nematicidal activity was due to DAPG and other metabolites might have caused the biocontrol effect.…”
Section: Discussioncontrasting
confidence: 99%
“…This resulted in poor growth and no production of DAPG, independent of the inorganic nitrogen source. These results are in contrast to results obtained by Siddiqui and Shaukat [ 26 ], who observed a nematicidal activity of filtrate from the DAPG-producing strain CHA0 when cultured on a medium lacking organic nitrogen. However, in their study it was not confirmed that the nematicidal activity was due to DAPG and other metabolites might have caused the biocontrol effect.…”
Section: Discussioncontrasting
confidence: 99%
“…2003) enhance the production of nematicidal agents in vitro and improve the biocontrol potential of P. fluorescens strain CHA0. Similarly, amino acids are also known to influence nematicidal activity by fluorescent pseudomonads in vitro (Siddiqui and Shaukat 2004b). Therefore, phenylalanine and asparagines were included in this experiment.…”
Section: The Effect Of a Methanol Fraction Of R Solani Culture Filtrmentioning
confidence: 99%
“…It has been reported in the last few decades that factors identified in vitro using liquid culture screening do indeed act as important virulence factors of phytopathogenic fungi and of microbial control agents such as entomopathogenic bacteria and entomopathogenic fungi (Bowen and Ensign, 1998;Fang et al, 2005;Siddiqui and Shaukat, 2004;St Leger et al, 1997;St Leger and Screen, 2001;St Leger and Wang, 2009). Based on this approach, most studies on the virulence factors of entomopathogenic fungi have been directed at elucidating the most relevant cuticledegrading enzymes (Griesch and Vilcinskas, 1998;Khachatourians, 1996;St Leger et al, 1996) because their overexpression in engineered strains results in more fungi that are more deadly towards insects (Fang et al, 2005;St Leger et al, 1996).…”
Section: Introductionmentioning
confidence: 98%